ANALISIS KESALAHAN PENGGUNAAN TANDA BACA DALAM SKRIPSI MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS NIAS RAYA OKTOBER 2022 - Nimerwati Gowasa (Universitas Nias Raya, 2024)
The background of the problem in this study is the misuse of punctuation marks such as punctuation periods, commas and colons in a sentence, then errors in spelling are found. The results of the study found that every student of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, University of Nias Raya had errors in using punctuation, 9 errors in writing a thesis, 8 comma punctuation errors in writing. Through this research it is recommended to; 1) Students to increase curiosity about Indonesian learning because it is related to everyday life. One of the implications of Indonesian learning is the use of punctuation marks that will definitely be used when writing: 2) Lecturers to always remind, motivate, and direct students to study seriously so that they are able to use good and correct Indonesian, both orally and in writing; 3) Nias Raya University Library so that it can facilitate students to be able to study optimally. Such as providing textbooks or stories that can add insight to students; holding writing competitions using good and correct Indonesian and spelling.